Hubungan Struktur Modal Dan Profitabilitas: Analisis Perusahaan Infrastruktur pada Indonesian Stock Exchange Tahun 2012-2016 - Eddy Winarso, Francis M. Hutabarat (Jurnal Akuntansi, 2018)
The purpose of this research is to analyze the relationship between capital structure and profitability of infrastructure companies listed in SMINFRA18 on the Indonesia Stock Exchange from 2012-2016. The advantage of an appropriate capital structure can help companies to grow primarily in the profits of their companies. This research is descriptive-correlation and quantitative approach. The data used in this study is the Capital Structure and Profitability Data of Infrastructure Companies in the Indonesia Stock Exchange which are members of the SMINFRA Index. There are 18 companies listed in the index which are the best companies in the infrastructure industry. The ratio used to describe the capital structure is Debt to Equity and the profitability ratio used is Return on Equity. This study uses statistical software to analyze: Auto-correlation, Multicollinearity, Normality, Heterocedascity, Correlation, and Regression analysis. Thus, the results of the study show that there is a significant relationship between capital structure and profitability in the SMINFRA18 Infrastructure Company listed on the Indonesia Stock Exchange.Keywords: Capital Structure, Profitability, Infrastructure, return on equity